Odpowiedzialność karna kontrolera Najwyższej Izby Kontroli za przestępstwo fałszu intelektualnego - Dziwisz, Stanisław (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The article analyses the elements of the crime of intellectual forgery, with particular emphasis on the criminal liability of auditors of the Supreme Audit Office (NIK) for certifying falsehood in the post-control statements. The author presents that NIK auditors are public officers within the meaning of Article 115 § 13 of the Polish Criminal Code (k.k.). It is also presented that the post-control statement is the document within the meaning of Article 271 k.k. and it contains a certification of the legally significant circumstances by an authorized person. The aim of this article is to demonstrate the possibility of imposing criminal liability for the crime described in Article 271 k.k. on the NIK auditors.